2009
DOI: 10.1016/j.vetmic.2008.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an outbreak of astroviral diarrhea in a group of cheetahs (Acinonyx jubatus)

Abstract: A Mamastrovirus was identified in an outbreak of diarrhea in cheetahs (Acinonyx jubatus). Five young adult and two adult cheetahs presented with lethargy, anorexia, watery diarrhea and regurgitation over an 11-day period. Fecal samples were submitted for electron microscopy and culture. Electron microscopy results revealed particles morphologically consistent with an astrovirus, and no other viral pathogens or significant bacterial pathogens were identified. The astrovirus was confirmed and sequenced using con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…This may represent a separate recombination event with an as-yet-unidentified clade of astroviruses. An analysis of the capsid region of a cheetah astrovirus found that it clustered relatively more closely with human astroviruses than was found in the analysis of the polymerase (Atkins et al, 2009). If due to a recombination event, this is an apparently opposite event from that seen in CslAstV-3, which has a human astrovirus-like polymerase and a CslAstV-2-like capsid, at least in the 59 end of ORF2.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This may represent a separate recombination event with an as-yet-unidentified clade of astroviruses. An analysis of the capsid region of a cheetah astrovirus found that it clustered relatively more closely with human astroviruses than was found in the analysis of the polymerase (Atkins et al, 2009). If due to a recombination event, this is an apparently opposite event from that seen in CslAstV-3, which has a human astrovirus-like polymerase and a CslAstV-2-like capsid, at least in the 59 end of ORF2.…”
Section: Discussionmentioning
confidence: 80%
“…Only very recently has the presence of astroviruses in wildlife hosts been reported (Atkins et al, 2009;Chu et al, 2008). Here, we report the first detection of five genetically distinct astroviruses from three marine mammal host species.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In most cases, viruses have been mostly isolated from healthy animals, and prevalences are high. The genetic diversity of feline AstVs (FAstVs), canine AstVs (CaAstVs), rabbit AstVs (RabAstVs), rat AstVs, and AstVs infecting sea lions and dolphins has not been studied so extensively, and the clinical impact of their infections seems to be low and has not been well explored yet (11,16,17,(196)(197)(198)(199)(200).…”
Section: Nonhuman Astrovirusesmentioning
confidence: 99%
“…However, later on, two genera were established based on their hosts of origin: Mamastrovirus (MAstV) and Avastrovirus (AAstV), infecting mammalian and avian species, respectively. Although initially detected in children's stool, AstVs have been found in the feces of a wide variety of mammalian species, i.e., cats (6), cattle (7), deer (8), dogs (9), mice (10), rats (11), pigs (12), sheep (13), mink (14), bats (15), cheetahs (16), rabbits (17), and even sea lions and dolphins (18), as well as in avian species, i.e., turkeys (19), chickens (20), ducks (21), pigeons (22), and guinea fowl (23) and other wild aquatic birds (24).…”
mentioning
confidence: 99%